Beyond teaching quality : Towards a framework for course unit quality. - Carbone, Angela; Evans, Julia; Ye, Jing (HERDSA Review of Higher Education v.3 p.57-72, 2016)
Global debates on teaching quality have prompted a focus on how university courses and subject units are designed, delivered and measured. However there is no unitary model that consolidates findings and offers a workable guide that can be used by universities and academics to improve learning and teaching. In this paper, a framework for developing and enhancing course units is presented, which highlights the concept of quality units that contributes to teaching quality. The concept of quality units goes beyond teaching practices and outcomes and includes additional factors. In constructing the Unit Quality Framework insights are drawn from research undertaken as part of an Australian Government Office for Learning and Teaching (OLT) sponsored National Senior Teaching Fellowship on the Peer Assisted Teaching Scheme (PATS). The Unit Quality Framework outlines the facets, underlying foundations, aspirational standards, barriers and evaluation lenses that guide unit development, assessments, teaching and evaluation. The paper provides insights into how the framework can be strategically adopted for institutional-wide reform of course units and the reinvigoration of teaching practices. [Author abstract]